Echocardiographic Assessment of Pulmonary Hypertension in Infants with Bronchopulmonary Dysplasia: Systematic Review of Literature and a Proposed Algorithm for Assessment. Issue 5 (18th September 2014) - Nagiub, Mohamed; Lee, Sam; Guglani, Lokesh
Abstract : Background: As survival and outcomes continue to improve in neonates born prematurely, there is an increasing need to promptly identify and treat pulmonary hypertension (PHT) in this population. Several echocardiographic indices have been used to evaluate for PHT. There is no clear consensus on how to utilize these parameters specifically for the evaluation of PHT in infants with chronic lung disease of prematurity. Objectives: Τhe objectives of the study were (1) to identify the different echocardiographic techniques for assessment of PHT in infants with chronic lung disease of prematurity in an evidence‐based manner and (2) to establish an echocardiographic screening protocol based on available literature using different echocardiographic techniques. Methods: We conducted a systematic review of the literature regarding use of echocardiographic techniques for evaluation of PHT in infants with bronchopulmonary dysplasia. On the basis of the available evidence, we came up with a screening algorithm using various echocardiographic techniques. Results: We identified nine techniques that had been employed for detection of PHT noninvasively using echocardiography in 23 studies. Using these echocardiographic parameters, we came up with a flow chart to diagnose PHT in infants born prematurely, based on presence or absence of tricuspid regurgitation, presence or absence of patent ductus arteriosus, and direction of flow. Conclusions: We have proposed a new screening strategy for assessment of PHT using echocardiography in infants with chronic lung disease of prematurity. Further studies will be necessary to confirm its validity.